The Adaptation of the 1.5 Generation of Chinese Immigrants in Spain - Shi, Zhilong (Sinología hispánica. China Studies Review, 2026)
Since the 1980s, Chinese immigrants in Spain have experienced rapid and steady growth, emerging as a significant part of Spanish society. In comparison to the first generation of Chinese immigrants who settled in Spain (parents), the 1.5 generation (children) exhibits more characteristics of Spanish life. However, due to the inherent Chinese attributes of the 1.5 generation Chinese immigrant population, inevitable cultural conflicts arise during the process of local socialization. In the clash of dual cultures, the question of “where do I belong” becomes a persistent source of identity confusion. This article takes the cultural interactions between the 1.5 generation immigrants and local Spanish culture as a starting point to explore the cultural adaptation of the new generation of Chinese immigrants in Spain. The research findings indicate that the 1.5 generation of Chinese immigrants in Spain faces challenges such as family separation, discrimination, and employment issue, but they demonstrate a strong commitment to family and the family business, and find a unique cultural identity between Spanish and Chinese culture.